Principles of digital audio - Pohlmann, Ken C. (Digital video/audio, 2011)
"Fully revised to cover the latest advances in digital audio. Offering a thorough survey of fundamentals and theory, Principles of digital audio, Sixth edition provides comprehensive coverage of today's leading digital audio technologies, including blu-ray, digital voice coding, recordable media, USB 2.0 audio, noise cancellation, room correction, media databases, streaming, and encryption. Written by well-known audio engineering expert and bestselling author Ken Pohlmann, the book has been extensively updated to reflect ongoing widespread changes in the audio industry. Chapters devoted to specific applications such as CD, DVD, and MP3 are included in this detailed guide. Principles of digital audio, sixth edition features: new chapters on blu-ray and digital voice coding. Expanded coverage of digital signal processing, discussing theory and applications. Complete update of both desktop and Internet audio. An extensive bibliography covers all digital audio topics: sound and numbers; fundamentals of digital audio; digital audio recording; error correction; optical disc storage; the compact disc; perceptual coding; DVD; blu-ray; audio interconnection; desktop audio; internet audio; digital radio and television broadcasting; digital voice coding; digital signal processing; Sigma-Delta conversion and noise shaping"